Correction: One-pot production of oxygenated monomers and selectively oxidized lignin from biomass based on plasma electrolysis. Issue 4 (7th February 2022) - A, Lusi; Radhakrishnan, Harish; Vincent Sahayaraj, Daniel; Tessonnier, Jean-Philippe; Hu, Hui; Bai, Xianglan
Abstract : Correction for 'One-pot production of oxygenated monomers and selectively oxidized lignin from biomass based on plasma electrolysis' by Lusi A et al., Green Chem., 2021, 23, 9109–9125, DOI: ; 10.1039/D1GC03315H .